Cholesterol efflux in the transplant patient. Issue 2 (April 2018) - Sudharshan, Sangita; Javaheri, Ali
Abstract : Purpose of review: Cholesterol metabolism is increasingly recognized in inflammatory diseases including transplantation. This review discusses the mechanistic underpinnings that tie macrophage cholesterol efflux capacity (CEC) of high-density lipoprotein (HDL) to chronic rejection in transplanted patients. Recent findings: Animal studies suggest that administration of apolipoprotein A-I, the main protein constituent of HDL, can prevent transplant arteriosclerosis. apoA-I administration increases CEC of HDL. In patients with cardiac allograft vasculopathy (CAV), decreased CEC has been associated with poorer survival. In addition, reduced CEC in recipients, pretransplant, has been associated with the development of CAV and renal allograft survival. Summary: These recent findings raise the hypothesis that increasing cholesterol efflux may prevent chronic rejection and improve allograft survival after transplant. Reconstituted HDL significantly increases CEC and is currently in clinical development for traditional atherosclerosis. Clinical trials of reconstituted HDL administration in transplantation should be performed.